Новый вид рода Sciapus (Diptera, Dolichopodidae) - Булли, А.Ф.; Негробов, О.П. (Вестник зоологии, 1987)
S. mediterraneus B u l l i et N e g r o b o v, sp. n.- differs in simple feet, partly yellow antennae, dark hypopygium, partly yellow abdomen, short honopodes and long dorsal hypopygial projections. T y p e - Io c a I i t y: Ukraine, Molochny Liman Estuary shore; 2 paratype males are from S. Armenia and Uzbekistan. Type material is deposited in Zoological Institute, USSR Academy of Sciences, Leningrad (including holotype) and Voronezh State University. Remove selected